A world review of the bee fly tribe Usiini (Diptera, Bombyliidae) — Part 3: Parageron Paramonov s. lat. - Gibbs, David (European Journal of Taxonomy, 2023)
This review covers Parageron Paramonov s. lat., including 36 species. Three new genera are proposed: Ectopusia gen. nov., Protypusia gen. nov. and Parusia gen. nov.; Parageron s. str. more narrowly defined. Eleven new species are described: Parageron longilingua sp. nov., Protypusia argentata gen. et sp. nov., Pro. separata Gibbs & Theodor gen. et sp. nov., Pro. flavipalpis gen. et sp. nov., Pro. kerkini gen. et sp. nov., Pro. strymonas gen. et sp. nov., Parusia almeria gen. et sp. nov., Pru. benoisti gen. et sp. nov., Pru. cyrenaica gen. et sp. nov., Pru. faesae gen. et sp. nov. and Pru. propinqua gen. et sp. nov. Two species raised from synonymy Par. orientalis Paramonov stat. rev. and Pru. taeniolata (Costa) stat. rev. Two species synonymised Pro. major Macquart syn. nov. and Usia arida Báez syn. nov. Eight species removed from Usiini to Apolysini, Apolysis bicolor (Efflatoun) comb. nov., A. elbae (Efflatoun) comb. nov., A. flavipes (Efflatoun) comb. nov., A. marginata (Brunetti) comb. nov., A. minuscula (Efflatoun) comb. nov., A. parvula (Efflatoun) comb. nov., A. turkmenica (Paramonov) comb. nov. and A. volkovitshi (Zaitzev) comb. nov. Apolysis melanderi Gibbs nom. nov. replaces A. bicolor (Melander) (was in Oligodranes) and A. hessei Gibbs nom. nov. replaces A. minuscula Hesse. Two neotypes and nine lectotypes are designated.